Titanium Mesh Exposure: A Case Report of Retrieved Underlying Soft Tissue and a Review of Literature: Titanium Mesh Exposure - Akhavan Azar, Bijan; Safiaghdam, Hannaneh; Gharehdaghi, Niusha; Khojasteh, Arash (Regeneration, Reconstruction & Restoration (Triple R), 2024)
Background and objectives: In this study, we aimed to report histopathological evaluation of the underlying tissues in a case of premature Titanium mesh exposure and assess the rate of Titanium mesh (Ti-mesh) exposure in the literature and its effect on treatment outcomes when used as a barrier membrane in jaw-bone reconstruction. Materials and methods: We reviewed articles that used Ti-mesh with/without grafting materials to reconstruct atrophic ridges both vertically and/or horizontally. Considering our inclusion criteria, 51 studies were included. All relevant RCTs, retrospective studies (cohorts and case-controls) and case-series were included but case-reports and review articles were excluded. Data regarding premature exposure rate, removal rate, associated bone loss, and implant survival rate were extracted. Later, a report of an early Ti-mesh exposure in anterior maxillary horizontal augmentation with autogenous bone graft and deproteinized bovine bone mineral in a 50-year-old female is presented with a histological study of the underlying soft tissue at the time of mesh removal. Results: A total of 51 studies were included in the review. Among the 41 studies reporting exposure, 18 reported removal of membranes, of which 3 caused significant bone loss. In the obtained biopsy from the reported case, a connective tissue infiltrated with sporadic inflammatory cells covered with keratinized stratified squamous epithelium was observed. Conclusion: Our results indicate the loss of outcomes (both bone loss and implant failure) may not be associated with Ti-mesh exposure, which could, along with the rate of exposure, help the clinician assess the relative risk of its application. Keywords: Alveolar ridge augmentation, Guided bone regeneration, Bone graft, Titanium mesh, Exposure.